Mountain lions on the prairie: habitat selection by recolonizing mountain lions at the edge of their range. Issue 5 (24th April 2019) - Gigliotti, Laura C.; Matchett, Marc R.; Jachowski, David S.
Abstract : Mountain lions ( Puma concolor ) have historically experienced large‐scale range contractions, but are beginning to recolonize portions of their former range. To reach potential suitable habitats in eastern North America, mountain lions need to move across the grassland and agriculture‐dominated habitats of the Great Plains, which are different from the forested areas associated with mountain lions in western North America. To inform restoration planning in this area, it is important to understand differences in mountain lion habitat selection in this "nontraditional" grassland habitat. We tracked GPS‐collared mountain lions in the Northern Great Plains of Montana and identified movement states (localized or exploratory) using behavioral change point analysis and net‐squared displacement. We compared habitat selection between the different states using step‐selection functions that included several environmental covariates. Similar to elsewhere throughout their range, across both movement states, mountain lions tended to select forested environments that were farther from human development. In contrast to more traditionally occupied mountainous regions, mountain lions in the Great Plains selected areas of lower elevations. They selected areas both near and far from water, but avoided riparian areas and selected more rugged environments when in exploratory movement states. This suggests that mountain lions in the Northern Great Plains are utilizing river corridors, particularly those with rough or broken topography during exploratory phases. To enhance future recolonization and connectivity of mountain lions to the east of our study area, we encourage managers to maintain and restore forest fragments along river corridors in the Great Plains.